Norma knjižne slovenščine med kodifikacijo in jezikovno rabo v obdobju 1950-2001 - Verovnik, Tina (Družboslovne razprave, 2004)
The study is an investigation into the conception of the Slovene written language norm over the last five decades of the 20th century, which coincide with the preparations for and the publications of the five fundamental codification manuals. The latter have always contributed to the clarification of notions concerning the written language norm, its source and characteristics. Therefore each period, defined by the given manual, is discussed in relation to the polemics and responses of the key authors, which provides an insight both into the broader linguistic situation and the development of the Slovene post-war normativist thought. The manuals are introduced from the perspective of the selection of the language material that served as the basis for their preparation, and the principles guiding their authors. With regard to their concept of and relation to the usage norm, we can roughly divide them into two groups: the regulative and the constitutive. Understanding of the two approaches and acquaintance with their history as well as their influence or effect upon the language use undoubtedly significantly contribute to the solving of the current linguistic issues
Keywords: Slovene; slovenščina; standard language; knjižni jezik; jezikovna norma; jezikovna pravila